Prevalence, causes and socio-economic determinants of vision loss in Cape Town, South Africa. - Nicky Cockburn; David Steven; Karin Lecuona; Francois Joubert; Graeme Rogers; Colin Cook; Sarah Polack (PLoS ONE, 2012)
PURPOSE: To estimate the prevalence and causes of blindness and visual impairment in Cape Town, South Africa and to explore socio-economic and demographic predictors of vision loss in this setting. METHODS: A cross sectional population-based survey was conducted in Cape Town. Eighty-two clusters were selected using probability proportionate to size sampling. Within each cluster 35 or 40 people aged 50 years and above were selected using compact segment sampling. Visual acuity of participants was assessed and eyes with a visual acuity less than 6/18 were examined by an ophthalmologist to determine the cause of vision loss. Demographic data (age, gender and education) were collected and a socio-economic status (SES) index was created using principal components analysis. RESULTS: Out of 3100 eligible people, 2750 (89%) were examined. The sample prevalence of bilateral blindness (presenting visual acuity <3/60) was 1.4% (95% CI 0.9-1.8). Posterior segment diseases accounted for 65% of blindness and cataract was responsible for 27%. The prevalence of vision loss was highest among people over 80 years (odds ratio (OR) 6.9 95% CI 4.6-10.6), those in the poorest SES group (OR 3.9 95% CI 2.2-6.7) and people with no formal education (OR 5.4 95% CI 1.7-16.6). Cataract surgical coverage was 68% in the poorest SES tertile (68%) compared to 93% in the medium and 100% in the highest tertile. CONCLUSIONS: The prevalence of blindness among people ≥50 years in Cape Town was lower than expected and the contribution of posterior segment diseases higher than previously reported in South Africa and Sub Saharan Africa. There were clear socio-economic disparities in prevalence of vision loss and cataract surgical coverage in this setting which need to be addressed in blindness prevention programs.